Plant ion channels: from molecular structures to physiological functions - Zimmermann, S.; Sentenac, H.
Progress in identification of plant ion channels and development of electrophysiological analyses in heterologous expression systems and in planta, in combination with reverse genetic approaches, are providing the possibility of associating molecular entities with physiological functions. Recently, the first attempts to determine in vivo functions using knockout mutants demonstrated the roles of root ion channels. The search for proteins interacting with such channels leads to an even more complex view of the concerted action in protein networks.